PERBEDAAN HUKUM KELUARGA MALAYSIA DAN BRUNEI DARUSSALAM - Ellisni Fikriyah; Siah Khoisyi’ah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Islamic family law plays an important role in regulating marriage, divorce, child custody, inheritance, and other family matters in Muslim societies. Malaysia and Brunei Darussalam both implement Islamic family law based on the Shafi'i school of thought, but their implementation shows differences due to differences in legal systems, government systems, and state policies regarding Islamic law. This study aims to examine the Islamic family law systems in Malaysia and Brunei Darussalam, analyze the differences in regulations regarding marriage, divorce, and the authority of judicial institutions, and identify factors that influence these differences. This study uses a qualitative method with a library research type and a comparative juridical approach. Data were obtained from laws and regulations, books, journals, and other relevant legal sources. The results show that Malaysia implements Islamic family law in a federal system influenced by common law, while Brunei Darussalam implements it more centrally under the ideology of Melayu Islam Beraja (MIB). These differences are seen in the regulation of the age of marriage, supervision of polygamy, divorce procedures, and the authority of the Sharia Court. The differences in the application of Islamic family law in the two countries are influenced by the governmental system, the history of legal development, demographic conditions, and state policies regarding Islamic law.